Toxicity levels in Spanish political communication on Twitter/X: a comparative analysis of major political parties, 2015–2023 - Amores, Javier J.; González-Baquero, William; Oller-Alonso, Martín (Frontiers in Political Science, 2025)
IntroductionSocial media, especially Twitter (now X), have long since become integral to the communication strategies of political parties, providing a direct and agile medium for interaction with the public and dissemination of messages. But this digital omnipresence also poses worrying challenges, such as the polarisation of political discourse. Several studies have explored the communication strategies of political parties on social media, as well as the toxic language and hate present in such communication. However, most of the work has looked at specific parties and in electoral contexts.MethodsThe present study focuses on examining in depth the levels of toxicity in political discourse on Twitter, particularly on the accounts of the 10 major Spanish political parties, from 2015 to 2023. Computational methods and the Google Perspective API have been used to identify the levels of toxicity, severe toxicity, insult, profanity, threat, and identity attack present in the contents published on these accounts during that period (N = 265,122).ResultsAmong the main findings, a generalized temporary increase in the presence of all toxicity indicators since 2015 is highlighted. Comparatively, a significant difference is perceived between most of the parties and Vox, the party that scores highest in virtually all indicators of toxicity. Furthermore, higher levels of toxicity appear to generate greater engagement in terms of interaction.DiscussionThese findings confirm trends noted earlier at the international level, such as the leading role of the populist far-right in the propagation of toxic discourses and the generalised rise of toxicity and polarization in political debate.